Pathobiology and Molecular Pathways Implicated in Osteosarcoma Lung Metastasis: A Scoping Review - Ala Bashir MD; Ayden Ismail MD; Avenie Mavadia MD; Aruni Ghose MD; Saak Victor Ovsepian PhD; Stergios Boussios MD, MSc, PhD, FRCP (Technology in Cancer Research & Treatment)
Osteosarcoma (OS) is the most common primary bone malignancy, with lung metastasis being the leading cause of mortality. The metastatic process is driven by complex biological mechanisms, including tumor cell-specific adaptations of growth pathways, immune modulation within the tumor microenvironment, and reactivation of metastatic cells from dormancy. This scoping review captures overlooked and under researched pathways, supporting mainstream therapeutic targets while shedding light on novel ones, reinforcing and revising conclusions drawn in previous literature, and guiding future research. MEDLINE, Embase, and Cochrane CENTRAL were searched with a publication date limit from 2019 onwards using relevant MeSH terms combined with Boolean operators, truncations, and keyword searches. The search culminated in 43 reports, including 30 in vivo, 8 in vitro, and 5 observational studies. This study conforms to the PRISMA-ScR guidelines. Tumor cell adaptations, including epithelial-mesenchymal transition (EMT) and enhanced migratory and proliferative signaling via JAK/STAT and TGF-β pathways, are critical drivers of OS lung metastasis. Manipulated upstream ligand-driven signaling promotes transcriptional changes that increase cell cycle proteins and mesenchymal markers, conferring chemoresistance and advancing OS cells toward a metastatic state. The tumor microenvironment also plays a key role; interactions between OS cell-derived cytokines and tumor-infiltrating immune cells lead to tumor associated macrophages and neutrophils (TAMs/TANs), which help establish a pre-metastatic niche and provoke immune remodeling. However, the impact of TAMs on OS survival remains ambiguous due to their dual pro- and anti-tumor roles. Lung-induced dormancy links tumor intrinsic and immune-driven mechanisms, allowing tumor cells to evade immunity or pause progression. Inflammatory pathways and immune activation can reverse dormancy, promoting further OS dissemination. The reviewed evidence supports targeting intracellular signaling and immune pathways to mitigate OS metastasis. The paucity of longitudinal data on lung dormancy warrants caution, emphasizing integrated approaches and better controlled studies with focus on combinatorial therapies for more conclusive outcomes.